Fundamental engineering mathematics:all stream except CSE and IT - Kar,Tapan Kumar (Santra Publications Pvt. Ltd., 2019)
Fundamental engineering mathematics:all stream except CSE and IT / Kar,Tapan Kumar. -- Kolkata: Santra Publications Pvt. Ltd., 2019 510 K18 No. of Copies : 1